2010
DOI: 10.1104/pp.110.159673
|View full text |Cite
|
Sign up to set email alerts
|

Digital Gene Expression Signatures for Maize Development    

Abstract: Genome-wide expression signatures detect specific perturbations in developmental programs and contribute to functional resolution of key regulatory networks. In maize (Zea mays) inflorescences, mutations in the RAMOSA (RA) genes affect the determinacy of axillary meristems and thus alter branching patterns, an important agronomic trait. In this work, we developed and tested a framework for analysis of tag-based, digital gene expression profiles using Illumina's high-throughput sequencing technology and the new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 76 publications
1
75
0
Order By: Relevance
“…The overall distribution of gene expression between pericarp and silk tissues is very similar and also very similar to genomewide expression patterns established for maize root, shoot, and leaf tissues (Eveland et al, 2010) (see Supplemental Figure 3 online). As anticipated, given that silks and pericarps have the same developmental origin, the ovary wall (Kiesselbach, 1980;Huang and Sheridan, 1994), the patterns of gene expression are more similar between pericarps and silks than with other plant organs (root, shoot, or leaf), with the difference in P1 genotype influencing gene expression patterns to a lesser extent than the origin of the tissue (see Supplemental Figure 3B online).…”
Section: P1 Controls Overlapping Yet Distinct Gene Sets In Maize Silkmentioning
confidence: 65%
“…The overall distribution of gene expression between pericarp and silk tissues is very similar and also very similar to genomewide expression patterns established for maize root, shoot, and leaf tissues (Eveland et al, 2010) (see Supplemental Figure 3 online). As anticipated, given that silks and pericarps have the same developmental origin, the ovary wall (Kiesselbach, 1980;Huang and Sheridan, 1994), the patterns of gene expression are more similar between pericarps and silks than with other plant organs (root, shoot, or leaf), with the difference in P1 genotype influencing gene expression patterns to a lesser extent than the origin of the tissue (see Supplemental Figure 3B online).…”
Section: P1 Controls Overlapping Yet Distinct Gene Sets In Maize Silkmentioning
confidence: 65%
“…Although RA2 and RA3 act independently in maize, we found that HvRA2 may regulate transcripts of HvSRA and T6P synthase, which in turn may regulate specific growth responses through synthesis of T6P (Fig. 4C) (27). Moreover, HvRA2 coopted a genus-specific function for the row-type pathway through regulation of Vrs1 (control over lateral spikelet fertility), thereby clearly indicating different gene sets and networks for inflorescence development compared with maize (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Our data suggest a model in which deletions in both maize genomes occur at the same overall rate, but purifying selection is (24). All P values were calculated using cumulative binomial distributions assuming an equal chance of gene copies on maize1 or maize2 dominating total expression for the gene pair.…”
Section: Discussionmentioning
confidence: 99%